The clinic application of mNGS and ENA-78 assays to identify intra-amniotic infection/inflammation - Di Shen; Di Shen; Hui Ju; Hongying Wang; Xietong Wang; Xietong Wang; Guangzhen Li (Frontiers in Cellular and Infection Microbiology)
ObjectiveThe objective of this study is to explore whether metagenomic next-generation sequencing (mNGS) and Epithelial Neutrophil Activating Peptide-78 (ENA-78) assays in the amniotic fluid (AF) of patients with preterm labor (PTL) could be employed for diagnosing intra-amniotic infection/inflammation (IAI/I) and predict the outcomes of emergency cerclage in women with cervical insufficiency(CI).MethodsAF samples from 40 patients were subjected to PTL were subjected to mNGS and microbial culture to diagnose intra-amniotic infection known as microbial invasion of the amniotic cavity (MIAC); ELISA was used to analyze ENA-78 levels for prediction of intra-amniotic inflammation (IAI). Pregnancy outcomes were compared, the predictive performance of mNGS and ENA-78 were assessed to evaluate the efficacy of emergency cervical cerclage.ResultsThe diagnosis rate of MIAC was higher with mNGS (17.5%) compared to microbial culture (2.5%). AF ENA-78 levels were significantly higher in IAI patients than in non-IAI/I patients. ENA-78 demonstrated certain accuracy in identifying IAI, with sensitivity and specificity of 73.3% and 100%, respectively. Compared with non-IAI/I patients, patients with MIAC or IAI exhibited poor pregnancy outcomes after cervical cerclage.ConclusionsmNGS and ENA-78 assays are valuable means for assessing the state of infection/inflammation in the amniotic cavity and predicting the outcomes of emergency cerclage.